IMPLIKASI PROGRAM BIMBINGAN PERKAWINAN DALAM PEMBENTUKAN KELUARGA SAKINAH: (Studi Kasus di KUA Kecamatan Gondang Kabupaten Mojokerto) - SAIFUL FUAD; AHMAD FARUQ (JOURNAL SAINS STUDENT RESEARCH, 2024)
. This research aims to determine the implications of marriage guidance in the formation of a sakinah family in the KUA of Gondang district. The author will explain the implications of marriage guidance in forming a sakinah family and the inhibiting and supporting factors in implementing marriage guidance. This research is qualitative research (Field Research) which is descriptive qualitative in nature. In obtaining data, the author used three data collection techniques, namely interviews, observation and documentation. The author uses data analysis techniques in the form of objective interpretations. The conclusion from the results of this research is that the implementation of marriage guidance for prospective brides and grooms in the KUA Gondang District, Mojokerto Regency has gone smoothly. There is a lot of material presented such as Munakahat Fiqh, Marriage, family planning and health. This marriage guidance program has a very positive impact on the formation of a sakinah family. Because of the existence of this program, the benefits can be felt in the families by participants who hold weddings at the KUA, Gondang sub-district. It is known that the Gondang District KUA has been very good at implementing government programs to help prospective brides and grooms prepare themselves properly and correctly before entering married life, namely by holding marriage guidance. However, the lack of awareness of the importance of this activity among prospective couples who are getting married is a factor inhibiting the activity itself.